An empirical evaluation of the capital asset pricing model in South Africa - Stewart, Alan James Harris (College of Accounting, 2023)
This thesis presents an empirical evaluation of the validity of the Capital Asset Pricing Model (CAPM) in South Africa. More specifically, the behaviour of share prices on the Johannesburg Stock Exchange during the eight years from 1973 to 1980 is evaluated. The study is the first direct test of the CAPM in South Africa. The methodology employed is a cross-sectional regression technique which has been used successfully in testing overseas security markets. An extension to the usual methodology is made by comparing the results obtained using a I published market-index with those obtained using an internally generated index. The historical development and the derivation of the CAPM is discussed in the thesis, as is the relationship between the CAPM and the Efficient Markets Hypothesis. The results indicate a strong possibility that the CAPM is a valid model in a South African context. Refinements to the research methodology strengthen this conclusion. A potential problem in the interpretation of the results of tests of this sort is also discussed, as is a recent extension to the theory. The overall conclusion is that the CAPM is a valid model, however further research is required to establish this with greater certainty.